Application of the MURDER learning model in mathematics classrooms: Effects on students' critical thinking abilities - Alam, Syamsu; ikram, Muhammad; Patmaniar, Patmaniar (Universitas Islam Raden Intan Lampung, INDONESIA, 2026)
Purpose: Fostering students' critical mathematical reasoning has emerged as a fundamental requirement in 21st-century mathematics education. Nevertheless, numerous students continue to encounter difficulties in logical reasoning, argument evaluation, and the formulation of reflective solutions to mathematical challenges. These challenges signify the necessity for educational methods that encompass cognitive dimensions while also fostering metacognitive awareness and emotional involvement in the learning process. This study seeks to examine the effect of the MURDER learning paradigm, comprising six organized stages (Mood, Understand, Recall, Digest, Expand, and Review), in improving students' mathematics critical-thinking abilities. Method: This study employed a quantitative approach using a quasi-experimental pretest–posttest control group design, encompassing 62 tenth-grade students from a public senior high school in South Sulawesi, Indonesia. Data were gathered using essay assessments, observation forms for students and educators, and expert-validated tools, which were analyzed using descriptive and inferential statistics. Findings: The findings indicate that the MURDER approach markedly enhanced students' mathematical critical thinking in comparison to conventional instruction. Students in the experimental group demonstrated higher engagement and stronger participation in reflective learning activities. These findings suggest that the structured stages of the MURDER model may support students’ critical-thinking processes during mathematics learning. Significance: This study provides classroom-based empirical evidence on the use of the MURDER learning model to support students’ mathematical critical thinking. The findings offer practical guidance for mathematics teachers in organizing instruction that integrates emotional readiness, conceptual understanding, collaborative discussion, and reflective review in secondary mathematics classrooms.